A cross-sectional survey on children perception of isolation methods for restorative procedures and influence of cognitive development - Anupam Saha; Rekhalakshmi Kamatham; Sreekanth Kumar Mallineni; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2016)
Aim: The aim of this study was to ascertain whether the cognitive level of a child affects the preference of isolation methods commonly employed in pediatric dentistry. Materials and Methods: Children from 4 to 16 years with no previous dental experience were recruited. Based on Piaget's stages of cognitive development, they were divided into three age groups, namely, Group I: 2-7 years, Group II: 7-11 years, and Group III: >11 years. Three videos demonstrating operative procedures performed under one of the isolation methods (1) rubber dam, (2) cotton rolls, and (3) saliva ejector were displayed and asked about their preference. The data were tabulated and statistically analyzed using Chi-square test for the difference in their preferences based on cognitive level of children. Results: A total of 360 children participated in the survey. Both 8-11 years and >11 years age group children preferred saliva ejector while 2-7 years group preferred rubber dam. Statistically, significant difference was observed (P < 0.001) among different age groups. No significant difference was observed between boys and girls regarding the preference to isolation techniques (P = 0.821). Most of the children preferred saliva ejector (P < 0.05). Conclusions: Children's perceptions and preferences are strongly influenced by the level of their cognitive development with children age 2-7 years preferred rubber dam whereas other age groups preferred saliva ejector.